The Influence of the Prodamas Program on Enhancing the Local Economy of Kediri City - Abubakar Abdullah; Theresia Pradini; Fathorrahman Fathorrahman (Universitas Negeri Surabaya, 2026)
This study aims to analyze the influence of community perception, participation, and mindset on the Community Empowerment Program (Prodamas) in enhancing the local economy of Kediri City. Prodamas is a form of budget decentralization that enables residents to be directly involved in planning, implementing, and evaluating development at the neighborhood level. Using a quantitative approach and multiple linear regression analysis with 100 respondents, the study reveals that community participation and mindset have a significant and positive effect on local economic growth, whereas perception does not have a direct impact. This research underscores the importance of active citizen involvement and a positive mentality as key determinants of the success of development programs. The recommendations emphasize strengthening community institutions and adopting more effective visual communication strategies.